Membangun Kesadaran Sanitasi Menuju Masyarakat Sehat dan Mandiri di RT 4 Desa Rejeki Kecamatan Palolo Kabupaten Sigi Provinsi Sulawesi Tengah - Fristalia, Mikaela Delpin; Kinasthy, Kinasthy; Gintu, Sinta; Zaitun, Zaitun; Almahdali, Intan Permata Sari; Agis, Merlin Wulandari; Tamira, Dian; Azzahra, Mayang; Irsal, Riskina Ayu; Balahanti, Regitha Cahyani Putri; L, Desiana Indrasari (Abdimas Indonesian Journal, 2024)
Public health is a complex and far-reaching issue, involving various factors that affect the overall health of individuals and communities. Some of the main public health problems that the group identified in Rejeki RT 4 Village, Palolo District, Sigi Regency, Central Sulawesi Province are environmental health such as the availability of bathing and washing facilities, clean water sources (bathing, drinking), access and visits to health service facilities which are very far away, and physical health problems, namely hypertension. Rejeki RT 04 village consists of 70 households with 318 recorded people. To assist the community in overcoming health problems in Rejeki RT 4 Village, community nursing practices were carried out to increase knowledge about healthy lifestyles by Group 15 which was carried out on August 18, 2024, in the form of health checks (physical programs), communication, information and education (non-physical programs) and providing additional nutrition to children (extra programs) where the realization of this implementation was 71%. The implementation of Real Work Lecture activities in Rejeki Village RT 4 Palolo District, Sigi Regency, Central Sulawesi Province went well with the collaboration between students, village government and local residents and educational institutions of Widya Nusantara University Palu. The results of this community service are expected to be useful for the people of Rejeki RT 4 Village, Palolo District, Sigi Regency, Central Sulawesi Province in dealing with physical health conditions experienced.